An evaluation of the music teacher candidates views regarding the projects carried on in the social service practice course - CAN, AJDA AYLİN (ELSEVIER SCIENCE BV, 2012)
The course Social Service Practices (SSP) which has been started to be instructed as a compulsory course in Education Faculties since 2006 in Turkey aims to contribute to train leader music teachers who are sensitive to the problems of the society, help to solve problems and teach to learn. In this research, which has aimed to determine the views of the students regarding the projects carried out by music teacher candidates in SSP course, the problem determination, planning, practice and assessment steps of the senior year music teacher candidates of Marmara University Ataturk Education Faculty 2010-2011 have been examined. The deficiencies stemming from non-fulfilment of the project management in the problem determination, planning, practice and assessment steps have been determined and solutions aiming to enhance the halting points have been offered.
Keywords: Education; Music; Education; Music Teacher; Social Service Practices